General hospital care for people with learning disabilities - Hannon, Lynn.; Clift, Julie (Chichester, West Sussex : Blackwell Pub., 2011)
'This book will provide nurses working in acute settings with a comprehensive resource for caring for people with a learning disability. The first chapter explores the nature of learning disability and highlights the specific health care needs of people with a learning disability. It summarises the current evidence-base, considers the key factors that influence the healthcare process, and stresses the importance of person-centred approaches. The book then takes the reader through the process of healthcare, through pre-admission assessment, care planning, intervention and treatment, liaison and discharge planning, highlighting key areas of healthcare need at each stage. This is followed by chapters on the key aspects of Communication, Understanding Behaviour, and the often difficult area of Consent. The book finishes with a chapter exploring the ethical and political aspects of care, the changing face of health services, interdisciplinary approaches, potential new roles and services that could be developed, and also highlights areas for future research.The book is relevant to the care of both children and adults with a learning disability and case vignettes are used throughout to illustrate situations. The book also includes reference to a research project looking at pre-admission assessment for people with a learning disability conducted by one of the authors' --Provided by publisher.
Machine generated contents note: Chapter 1. Understanding Learning Disability Definitions, causes, and range of conditions associated with learning disability Perceptions and attitudes towards people with a learning disability Health needs of people with a learning disabilityIntroduction to Person-Centred Approaches. Chapter 2. The Process of Healthcare The Patient Journey Pre-admission Care planning Intervention and treatment Liaison and Discharge Planning. Chapter 3. Communication Communicating with people with a learning disability Developing relationships Models of communication - verbal and non-verbal Tools to aid communication. Chapter 4. Understanding Behaviour What could different behaviours mean? Behavioural signs and symptoms How hospital admission can affect individual behaviour and ways of overcoming this. Chapter 5. Consent The law on consent and capacity to consent (In England and Wales) Obtaining consent Advocacy and empowerment Emergency situations What to do when consent is refused. Chapter 6. Ethical and Political Aspects of Care Healthcare ethics and professional accountability Political issues affecting service provision in both learning disability and secondary care services Interdisciplinary approaches and partnership working: Where do we go from here?
Keywords: Learning Disorders -- nursing; Hospitalization